2020
DOI: 10.1007/s00414-020-02262-8
|View full text |Cite
|
Sign up to set email alerts
|

The punched-out tissue complex (skin-bone ”imprimatum“) in shots from captive-bolt guns: does it act as a secondary projectile?

Abstract: From the first half of the twentieth century to the present day, injuries and fatalities from captive-bolt livestock stunners are a major topic in forensic medicine. The vast majority of cases account for suicides with the frontal, temporal, parietal, and occipital regions being the most common sites of entrance (in descending order of frequency). Due to the limited length of the bolt, the corresponding wound channel within the braincase is only several centimeters long. It has been a controversial subject for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Thus, the BigBovid with the .357 MAG FTX ® offers a clear advantage over conventional captive-bolt stunners, which are less precise in terms of damaging the corresponding brain regions ( 15 , 16 ). In ballistic experiments it is shown that the temporary wound cavity caused by a captive-bolt stunner in ordnance gelatin narrows in depth ( 17 ), and therefore the bolt must penetrate the brain tissue, if not directly, at least near the relevant brain regions. In terms of penetration depth, the fragments of the .357 MAG FTX ® had a minimum value of 9.37 cm and a maximum value of 14.38 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the BigBovid with the .357 MAG FTX ® offers a clear advantage over conventional captive-bolt stunners, which are less precise in terms of damaging the corresponding brain regions ( 15 , 16 ). In ballistic experiments it is shown that the temporary wound cavity caused by a captive-bolt stunner in ordnance gelatin narrows in depth ( 17 ), and therefore the bolt must penetrate the brain tissue, if not directly, at least near the relevant brain regions. In terms of penetration depth, the fragments of the .357 MAG FTX ® had a minimum value of 9.37 cm and a maximum value of 14.38 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Composite models made from a gelatin matrix and enclosed organs or (synthetic) bones have repeatedly been used to simulate the interaction between a bullet and a compound biological target [ 20 , 23 , 27 ]. By this means, it was possible to answer the question whether bone fragments act as “secondary projectiles” having the potential to create own wound channels [ 18 ]. Another point of debate was the displacement of tissue particles along the bullet path [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Captive-bolt guns are used to stun cattle before slaughter and are sometimes used in suicides. It was explored whether the ‘plug’ of skin and bone that is pushed out by the bolt in a cranial shot can penetrate beyond the depth is pushed in by the bolt and acts like a secondary projectile in that sense [ 154 ]. The study indicates that it does not.…”
Section: Wound Ballisticsmentioning
confidence: 99%